3D printing of aluminum oxide via composite extrusion modeling using a ceramic injection molding feedstock. (March 2023) - Dreier, Tim; Riaz, Abdullah; Ahrend, Alexander; Polley, Christian; Bode, Stefanie; Milkereit, Benjamin; Seitz, Hermann
Graphical abstract: Highlights: The production of additively manufactured parts using a screw-based MEX printer using a conventional ceramic injection molding (CIM) feedstock was demonstrated. Debinding and sintering steps from injection molding could be successfully transferred to the additively manufactured components. 3D printed parts reached a relative density of > 99% compared to conventional injection molding process. The structured approach to parameter identification can serve as a basis for determining screw-based MEX process parameters for other conventional feedstocks as well. Abstract: Composite Extrusion Modeling (CEM) is a screw-based material extrusion (MEX) additive manufacturing process that can produce plastic, metal and ceramic parts based on standard injection molding feedstocks. In this work, an aluminum oxide feedstock (Al2 O3 ) originally developed for injection molding is processed via a screw-based MEX process for the first time by depositing the plasticized material in layers on the build platform. In order to identify appropriate process parameters, the feedstock is first characterized to estimate the printable temperature processing window. Initially, the best printable extrusion values were estimated in terms of green part density and dimensional accuracy. Afterwards, different nozzle diameters and layer heights are investigated to further improve the green part density and shape accuracy. An extrusion multiplier of 0.14, nozzle diameter of 0.4 mm and a layer height of 0.1 mm were found to be the optimum process parameters to achieve highly dense green parts with a density of 2.791 ± 0.001 g/cm 3 . The optimized parts were also debound and sintered and the shrinkage was investigated. A shrinkage of 17.43% in the z direction and 14.08% in the x-y direction was observed, and a density of 3.92 ± 0.0025 g/cm 3 was achieved for the sintered parts.